(untitled) (Prosiding SEMDIKJAR (Seminar Nasional Pendidikan dan Pembelajaran), 2025)
This research is motivated by learning that is still dominated by lecture activities. As a result, the classroom atmosphere is monotonous, passive, and boring. This is evident from the lack of student learning outcomes. This study aims to determine the validity, practicality and effectiveness of interactive learning media based on Augmented Reality in social studies lessons on natural phenomena and livelihoods. This research method uses Research and Development (R&D) using the ADDIE development model (analysis, design, development, implementation, evaluation). The results of this study were declared valid, obtained from media experts 96% and material experts 94%, with an average validity of 95%. It was declared practical, obtained from the results of teacher responses 94% and student responses 95.1% with an average practicality of 94.55%. And it was declared very effective in the broad test with the results of the pre-test score of 58.2 and post-test 87, and analyzed with N-Gain got a score of 0.71 which is classified as "high" criteria. Based on the results of the research that has been conducted, it can be concluded that AR-based interactive learning media is effective in improving learning outcomes in the material on natural phenomena and livelihoods of grade IV students.